Syngas production by bi-reforming methane on an Ni–K-promoted catalyst using hydrotalcites and filamentous carbon as a support material - Cunha, Adelino F. (2021)
Steam reforming of methane (SRM) and dry reforming of methane (DRM) are frequently used in the production of syngas; however, the bi-reforming of methane (BRM) is an interesting and alternative process. In this study, BRM was studied over MgO, a layered double hydroxide (LDH) phase that was destroyed between 600 °C and 900 °C during the reaction. It showed good sorption capacity for CO2 at relatively low temperatures (<500 °C), with CO2 adsorption being a pre-requisite for its catalytic conversion. Among the tested materials, the potassium-promoted LDH showed the highest activity, achieving a maximum CO2 conversion of 75%. The results suggest that at high temperature, the electronic structure of the used materials influences the destabilization of the feed in the order of methane, water and carbon dioxide. K promotes the catalytic activity, compensates the presence of large Ni particle sizes originating from the high metal loading, and favors the formation of Mg–Al-spinel. K is known to be an electronic promoter that releases electrons, which flow to the active metal. This electron flow induces instability on the molecule to be converted, and most probably, also induces size variations on the respective active nickel metal. The influence of the operating conditions in the range of 300 °C to 900 °C on the conversion of the reactants and product distribution was studied. Accordingly, it was concluded that it is only possible to obtain molar ratios of hydrogen-to-carbon monoxide close to two at high temperatures, a pre-requisite for the synthesis of methanol.